Retrofit of Masonry Structures with Seismic Control Methods and Architectural Design Requirements - Günay, Hilal; Torunbalcı, Necdet (American Society of Civil Engineers (ASCE), 2023)
Seismic loads pose a great risk to existing masonry buildings. Modern seismic control methods that are being increasingly used today, rather than various traditional strengthening methods, appear in the retrofit of existing masonry structures. The use of seismic control in existing masonry buildings increases the functionality of the building and obviates the need for additional structural requirements. Particularly, seismic control methods are superior because they contain the least possible interventions to architectural details. On the other hand, these methods are a unique option in sensitive structures such as historical masonry structures. In this research, base isolation systems, energy-damping systems, and hybrid systems as well as architectural application details of seismic control methods in masonry structures are discussed in the context of architectural details.
Keywords: Earthquake; Masonry Structure; Base Isolation System; Energy-damping System; Energy Dissipation System; Hybrid System; Modern Seismic Retrofit